3 Records of the Colony of Rhode Island, and Providence Plantations, in New England 31 (1858) - (:unkn) unknown (My University, 1679)
And bee it further enacted by the authority aforesaid, That any person or persons shall presume to sport, game or play at any manner of game or games, or shooting on the first day of the weeke as aforesaid, or shall sit tippling and drinking in any tavern, ale-house, ordinary or victualling house on the first day of the weeke, more than necessity requireth;
Keywords: SABBATH-BREAKING LAW